Recruitment of First Level Court Judges in a State Administration Perspective in Indonesia - Hendi Gusta Rianda (Fakultas Hukum Universitas Lampung, 2020)
The ups and downs and political configurations that have occurred in Indonesia since the old order, the new order until the reformation have affected the judicial power system in Indonesia and thus have an impact on the recruitment of first-level court judges. This study aims to determine the recruitment of first-level court judges since the old order until the issuance of the Constitutional Court Decision Number 43/PUU-XIII/2015. This type of research is a normative juridical research by assessing the historical approach and the comparative approach. The results showed that after the Constitutional Court decision Number 43 / PUU XIII / 2015, the recruitment of first-level court judges by the Supreme Court in 2017 was still with the same recruitment pattern as before, namely state civil servants.